Inherited factor II deficiency with paradoxical hypercoagulability: a case report. Issue 2 (March 2018) - Watson, Harold; Perez, Ariel; Ayesu, Kwabena; Musa, Faisal; Sarriera, Jose; Madruga, Mario; Carlan, Steve J.
Abstract : N/A: Congenital deficiency of factor II is a very rare autosomal recessive disorder that can result in a bleeding diathesis. Genotypically, individuals are either homozygous for a defective prothrombin gene or a compound heterozygote with different mutated prothrombin genes inherited from each parent. Phenotypically, it is characterized by either a low production of normal prothrombin or a near-normal production of dysfunctional prothrombin. Treatment is aimed at restoring normally functioning factor II circulating levels to sufficient concentration for hemostasis. Paradoxical thrombosis in patients born from a nonconsanguineous marriage with factor II deficiency has not been reported. A woman with known congenital factor II deficiency confirmed by history and hemostatic laboratory analysis presented with an unprovoked spontaneous thrombosis of the common femoral vein detected on color Doppler. Venous thrombosis can occur in congenital deficiency of factor II and inferior vena cava filter can be life-saving.